The Role of Mobile Network Operators in Intelligent Transport Systems: Situation Analysis, Challenges and Suggested Approach - Athanasios Karapantelakis; Jan Markendahl (International Telecommunications Society (ITS), 2015)
In recent years, the role of Information and Communications Technology (ICT) in automotive has been accentuated, as services requiring vehicle-to-infrastructure (“V2I”) networks to communicate with off-board software have been multiplying. While current legislation, policies and network infrastructure generally limit such off-board services to infotainment (for example in-vehicle hotspots for media streaming, web browsing from passenger mobile devices) for safety and security reasons, many industry analysts but also the research community predict that the automotive landscape of 2025 will be different. Next generation mobile networks are expected to provide the necessary quality of service (e.g. low latency, high throughput) to support a broad range of applications, from infotainment to mission-critical telematic applications that involve partial or full remote vehicle control. At the same time, such mission-critical applications have already started to appear as Proof-of-Concepts (PoCs), in controlled environments (for example controlled sections of highways, or test tracks). In this paper, we investigate the role of Mobile Network Operators (MNOs) in such applications. The paper starts from an overview of the current status of automotive/ICT industry from a market, policy and technology perspective. Subsequently, we present results from a study of two use cases performed within Ericsson Research. The authors use learnings from these use cases and the current industry status to form a general understanding on the challenges that MNOs will face as network infrastructure providers for automotive applications, as well as strategic options for MNOs to address these challenges.
Keywords: 330